High-performance work systems and psychosocial safety climate influence work engagement through job satisfaction pathways - Larasandi, Dhiny Sartika; Satrya, Aryana (Annals of Human Resource Management Research, 2025)
Purpose: This study aims to analyze the mechanisms through which high performance work systems and psychosocial safety climate affect employee work engagement with the consideration of job satisfaction as mediator in TIC sectors. Methodology: A sample of 334 employees working across several provinces in Indonesia was surveyed, and Partial Least Squares Structural Equation Modelling was applied to analyze the data using Smart-PLS. Results: The results confirmed both HPWS and PSC did not have a positive direct effect on work engagement. However, they had a positive indirect effect, respectively, on work engagement by increasing job satisfaction. Conclusions: Thus, confirming the role of full mediation of job satisfaction. This study provides the first evidence of the comprehensive integration of two independent variables of HPWSs and PSC with mediation job satisfaction in one model, which has never been done in any previous studies, to employee outcomes in the context of service sectors, and it contributes to the field with important theoretical contributions, as well as managerial recommendations. Limitations: This study is limited in the use of cross sectional, self report. Contribution: The contribution: there has never been a previous study that integrates these 4 variables in one whole theoretical model. Literacy contribution, for the TIC (testing inspection certification business services sector, especially in the HR department.